A simple method to make, trap and deform a vesicle in a gel - Pierre Tapie; Alexis M. Prevost; Lorraine Montel; Léa-Laetitia Pontani; Elie Wandersman (Scientific Reports, 2023)
Abstract We present a simple method to produce giant lipid pseudo-vesicles (vesicles with an oily cap on the top), trapped in an agarose gel. The method can be implemented using only a regular micropipette and relies on the formation of a water/oil/water double droplet in liquid agarose. We characterize the produced vesicle with fluorescence imaging and establish the presence and integrity of the lipid bilayer by the successful insertion of $$α $$ α -Hemolysin transmembrane proteins. Finally, we show that the vesicle can be easily mechanically deformed, non-intrusively, by indenting the surface of the gel.